Comparison between uses of topical tacrolimus and triamcinolone ointment for the treatment of oral lichen planus. (Update Dental College Journal, 2018)
Background: Lichen planus is a chronic mucocutaneous disease with primary or secondary involve- ment of the oral mucosa. In particular in case of erosive lichen planus most of the patients experience no long term symptoms relief of conventional topical treatment such as corticosteroid ointment. Topical tacrolimus applications to mucosal lesions seem to be an alternative treatment approach.Objective: The aim of this study was to compare the efficacy of topical tacrolimus ointment with that of triamcinolone acetonide ointment on patients suffering from oral lichen planus.Study design: This was a clinical trial.  Study setting and period: This study was conducted in outpatient department of Oral and Maxillofacial Surgery, Dhaka Dental College in the period between June 2013 to May 2014.Subjects: A total of sixty patients were enrolled. Out of sixty patients thirty patients used topical tacroli- mus 0.03% (Group A) and another thirty patients used topical triamcinolone acetonide( Group B) for the treatment of oral lichen planus.Methods: A total of sixty patients were asked to answer a questionnaire regarding the degree of pain and burning sensation in every two weeks according to visual analogue scale (VAS). In every two weeks change of colour and size and also any side effects of these drugs were assessed. Data were analyzed using Statistical Package for Social Science (SPSS), version 15.0 for windows.Results: At the end of 12th week follow up periods complete relief of pain and burning sensation in group A patients were 100% and in group B it was 30%. There was no side effect in two study group patients.Update Dent. Coll. j: 2018; 8 (1): 17-21